Fine root distribution, characteristics and rhizosphere soil properties in a mixed stand of Robinia pseudoacacia and Fraxinus velutina in a saline soil - Du, Zhen-Yu; Wang, Qing-Hua; Xing, Shang-Jun; Liu, Fang-Chun; Ma, Bing-Yao; Ma, Hai-Lin; Liu, De-Xi (Silva Fennica, 2013)
The spatial distribution and characteristics of fine roots (< 2 mm in diameter), and rhizosphere soil properties were studied in a mixed planted forest of black locust ( L.) and velvet ash ( Torr.) 27 years after planting in a coastal saline soil of the Yellow River delta, China. The results of fine root analysis showed that the fine roots of both black locust and velvet ash were mainly distributed in the soil layer at 0â20 cm depth and 50â150 cm from trees. The fine root distribution of both species suggests a strategy of avoiding salinity rather than salt âtolerance. The horizontal spread distance of fine roots of velvet ash was evidently longer than that of black locust. The fine root biomass, specific root length, specific root area, specific root volume and root activity were significantly higher for velvet ash in comparison with black locust. The results of soil analysis showed that rhizosphere soil pH of black locust and velvet ash were significantly lower compared with non-rhizosphere soil. The available N content in rhizosphere soil of black locust was higher than that of velvet ash. However, the contents of soluble salt, organic matter, available P and available K in rhizosphere soil of velvet ash were higher than those of black locust. The above results indicated that the differences between black locust and velvet ash in fine root distribution, characteristics and rhizosphere soil properties were the major reasons for that velvet ash showed stronger acclimation responses than black locust to the coastal saline soil.Robinia pseudoacaciaFraxinus velutina